Publisher Correction: The sea lamprey germline genome provides insights into programmed genome rearrangement and vertebrate evolution. (November 2018) - Smith, Jeramiah; Timoshevskaya, Nataliya; Ye, Chengxi; Holt, Carson; Keinath, Melissa; Parker, Hugo; Cook, Malcolm; Hess, Jon; Narum, Shawn; Lamanna, Francesco; Kaessmann, Henrik; Timoshevskiy, Vladimir; et al.
When published, this article did not initially appear open access. This error has been corrected, and the open access status of the paper is noted in all versions of the paper. Additionally, affiliation 16 denoting equal contribution was missing from author Robb Krumlauf in the PDF originally published. This error has also been corrected.